Thermoelectric nanowires: A brief prospective. (15th January 2016) - Caballero-Calero, Olga; Martín-González, Marisol
Graphical abstract: Abstract: Nanowire structures have been investigated in order to achieve improved thermoelectric performance of thermoelectric materials. This brief viewpoint article summarizes the progress done in the last years and our vision of which are the key points to achieve a future generation of efficient nanowire-based thermoelectric devices.